Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(5^2+3^2).x+(5^2-3^2).x-40=10^2
34x+16x-40=100
50x-40=100
50x=140
x=14/5
Bài 1:
a) \(2^8.2.4=2^9.2^2=2^{11}\)
b) \(8^5:64=8^5:8^2=8^3\)
c) \(3^7:9=3^7:3^2=3^5\)
d) \(9^{17}.81=9^{17}.9^2=9^{19}\)
e) \(x^6.x.x^2=x^9\)
Bài 2:
a) \(2^x-15=17\)
\(\Rightarrow2^x=32\)
\(\Rightarrow2^x=2^5\)
\(\Rightarrow x=5\)
Vậy x = 5
b) \(2.3^x=162\)
\(3^x=162:2\)
\(3^x=81\)
\(\Rightarrow3^x=3^4\)
\(\Rightarrow x=4\)
Vậy x = 4
c) \(5.x.5^2=10\)
\(\Rightarrow x.5^3=10\)
\(\Rightarrow x.125=10\)
\(\Rightarrow x=10:125\)
\(\Rightarrow x=\frac{2}{25}\)
Vậy \(x=\frac{2}{25}\)
d) \(5.x^2-1=124\)
\(\Rightarrow5.x^2=125\)
\(\Rightarrow x^2=125:5\)
\(\Rightarrow x^2=5^2\)
\(\Rightarrow x=\pm5\)
Vậy \(x=\pm5\)
Câu 1:
a)28.2.4=28.2.22=211
b)85:64=85:82=83
c)37:9=37:32=35
d)917.81=917.92=919
e)x6.x.x2=x9
\(\left(5^2+3^2\right).x+\left(5^2-3^2\right).x-40.x=10^2\)
\(\Rightarrow\left(25+9\right)x+\left(25-9\right)x-40x=100\)
\(\Rightarrow34x+16x-40x=100\Rightarrow\left(34+16-40\right)x=100\)
\(\Rightarrow10x=100\Rightarrow x=100\div10=10\)
Vậy \(x=10\)
Đặt \(A=5+5^3+5^5+....+5^{47}+5^{49}\)
\(\Rightarrow5^2A=5^3+5^5+5^7+.....+5^{49}+5^{51}\)
\(\Rightarrow5^2A-A=\left(5^3+5^5+5^7+....+5^{49}+5^{51}\right)-\left(3+3^3+3^5+....+5^{47}+5^{49}\right)\)
\(\Rightarrow24A=5^{51}-5\)
\(\Rightarrow A=\dfrac{5^{51}-5}{24}\)
Vậy ............................................................
1)a) \(\left(3x-7\right)^5=32\Rightarrow\left(3x-7\right)^5=2^5\)
\(\Rightarrow3x-7=2\Rightarrow3x=9\Rightarrow x=3\)
Vậy \(x=3\)
b) \(\left(4x-1\right)^3=-27.125\)
\(\Rightarrow\left(4x-1\right)^3=-3^3.5^3=-15^3\)
\(\Rightarrow4x-1=-15\Rightarrow4x=-14\Rightarrow x=-3,5\)
Vậy \(x=-3,5\)
c) \(3^{4x+4}=81^{x+3}\Rightarrow3^{4x+4}=3^{4x+12}\)
\(\Rightarrow4x+4=4x+12\)
\(\Rightarrow4x=4x+8\)
\(\Rightarrow x\in\varnothing\)
d) \(\left(x-5\right)^7=\left(x-5\right)^9\)
\(\Rightarrow\left(x-5\right)^7-\left(x-5\right)^9=0\)
\(\Rightarrow\left(x-5\right)^7.\left[1-\left(x-5\right)^2\right]=0\)
\(\Rightarrow\left[{}\begin{matrix}\left(x-5\right)^7=0\\1-\left(x-5\right)^2=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=5\\\left(x-5\right)^2=1\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=5\\x-5=-1\\x-5=1\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=5\\x=4\\x=6\end{matrix}\right.\)
Vậy \(\left[{}\begin{matrix}x=5\\x=4\\x=6\end{matrix}\right.\)
7(x-9)-5(6-x)=-6+11x
7x-63-30-5x=-6+11x
(7x-5x)-(63+30)=-6+11x
\(\Rightarrow\)2x-93=-6+11x
\(\Rightarrow\)6+93=11x-2x
99=9x
\(\Rightarrow\)x=99:9
x=11
\(5^x.5^2=5^{40}\)
\(\Rightarrow5^x=5^{40}:5^2=5^{38}\)
=> x = 38
\(5^x\cdot5^2=5^{40}\)
\(\Leftrightarrow x+2=40\)
hay x=38